MiR‐181 elevates Akt signaling by co‐targeting PHLPP2 and INPP4B phosphatases in luminal breast cancer. Issue 10 (11th March 2017) - Strotbek, Michaela; Schmid, Simone; Sánchez‐González, Ismael; Boerries, Melanie; Busch, Hauke; Olayioye, Monilola A.
Abstract : The PI3K‐Akt pathway is one of the most commonly dysregulated cancer‐associated signaling pathways. Here we report an oncogenic function for the miR‐181 family in luminal breast cancer cells that involves Akt hyperactivation. We show that miR‐181a and miR‐181d posttranscriptionally suppress the expression of PHLPP2 and INPP4B phosphatases, resulting in elevated growth factor‐induced Akt phosphorylation. Ectopic expression of miR‐181a and miR‐181d promoted S‐phase entry and cell proliferation, which was reversed by pharmacological Akt inhibition. Importantly, the expression of miR‐181 family members and PHLPP2/INPP2B are inversely correlated in primary human estrogen receptor‐positive breast cancers, supporting the clinical relevance of our findings. Abstract : What's new? The PI3K‐Akt pathway is one of the most commonly dysregulated signaling pathways in cancer. Here, the authors reveal molecular mechanisms whereby the miR‐181 family members contribute to PI3K‐Akt pathway activation. The increased expression of miR‐181 family members in luminal breast cancer inversely correlates with the expression of PHLPP2 and INPP4B, both tumor‐suppressive phosphatases that negatively regulate the PI3K survival pathway. Experimental evidence shows that miR‐181 overexpression hyperactivates PI3K‐Akt signaling and stimulates growth through the pathway. Combining antiestrogen treatment with PI3K pathway inhibitors may thus represent a promising strategy for the treatment of luminal breast cancers with high miR‐181 expression levels.